2009
DOI: 10.1002/mmce.20388
|View full text |Cite
|
Sign up to set email alerts
|

Probe compensated single feed circularly polarized fractal-shaped microstrip antennas

Abstract: A single feed circularly polarized fractal boundary microstrip antenna with improved axial ratio bandwidth is presented. The low-axial ratio bandwidth of single feed circularly polarized microstrip antenna is due to its probe reactance. In this article, the inherent disadvantage of this low-AR bandwidth is overcome by compensating the probe reactance by incorporating capacitance in the form of small patch between the radiating patch and the probe. The perturbation of the patch is done using fractal curve as bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Here, n is the total number of ports, k is the port numbering index, and ak is a complex number representing magnitude and phase for the kth source. From formulae 1 and , we know that the active VSWR of one port is achieved when the other three ports are also excited simultaneously. In this case, the matching behavior of one port is actually affected by the impedance mismatch of one port itself and the mutual coupling among the other three ports.…”
Section: Antenna Operating Principle and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, n is the total number of ports, k is the port numbering index, and ak is a complex number representing magnitude and phase for the kth source. From formulae 1 and , we know that the active VSWR of one port is achieved when the other three ports are also excited simultaneously. In this case, the matching behavior of one port is actually affected by the impedance mismatch of one port itself and the mutual coupling among the other three ports.…”
Section: Antenna Operating Principle and Discussionmentioning
confidence: 99%
“…Generally, CP antennas can be categorized into single‐fed type and multi‐fed type according to their feeding methods. For the single‐fed type, many microstrip CP antennas have been proposed . It can be observed that all of them have narrow impedance and axial ratio (AR) bandwidths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation